Synthesis, Characterization and Molecular Docking Studies of 5-Chloro-1-(1H-indole-2-yl)-3-methyl-4,5-dihydro-1H-pyrazole-4-carboxylic Acids - Ganga Reddy, G.; Ramakrishna Reddy, S.; Venkata Ramana Reddy, Ch.; Laxminarayana, E.; Srinivasa Reddy, B. (Asian Journal of Chemistry, 2022)
A series of new 5-chloro-1-(1H-indole-2-yl)-3-methyl-4,5-dihydro-1H-pyrazole-4-carbxylic acids (5a-c) was synthesized. For the synthesis of these compounds, the 1H-indole-2-carboxylic acids (1a-c) were used as core compound. The synthetic route leading to the title compounds is summarized in Scheme-I. The chemical structures of all intermediates and products were confirmed by their IR, 1H and 13C NMR, mass spectral data and elemental analysis. The molecular docking studies of title compounds was carried out to predict the binding interactions with target protein EGFR.